Intergrowth of Components and Ramps in Coffin-Shaped ZSM-5 Zeolite Crystals Unraveled by Focused Ion Beam-Assisted Transmission Electron Microscopy - Lu, Jiangbo; Roeffaers, Maarten B.J.; Bartholomeeusen, Evelyne; Sels, Bert F.; Schryvers, Dominique (Microscopy and microanalysis, 2014)
Scanning electron microscopy, focused ion beam (FIB), and transmission electron microscopy are combined to study the intergrowth of 90° rotational components and of ramps in coffin-shaped ZSM-5 crystals. The 90° rotational boundaries with local zig-zag features between different intergrowth components are observed in the main part of crystal. Also a new kind of displacement boundary is described. At the displacement boundary there is a shift of the unit cells along the boundary without a change in orientation. Based on lamellae prepared with FIB from different positions of the ramps and crystal, the orientation relationships between ramps and the main part of the crystal are studied and the three-dimensional morphology and growth mechanism of the ramp are illustrated.